Evaluation of hepcidin as a biomarker for the differential diagnosis of iron deficiency anaemia and anaemia of chronic disease - Chikwanda, Ephraim; Daka, Victor; Simakando, Marah; Kowa, Sumbukeni; Kaile, Trevor (Asian Journal of Medical Sciences, 2018)
Background: Anaemia affects approximately 1.62 billion people globally corresponding to 24.8% of the world’s population. Iron deficiency anaemia (IDA) and anaemia of chronic disease (ACD) are the most common forms of anaemia. A hormone produced by the liver, hepcidin, is the primary regulator of iron homeostasis and its production increases in ACD and decreases in IDA. Usually, ACD and IDA coexist and sometimes look identical on peripheral blood smears. Aims and Objectives: The current study aims to evaluate the diagnostic value of hepcidin to predict ACD from IDA as well as the diagnostic value of hepcidin to predict ACD from a combination of IDA and ACD. Materials and Methods: Specimens presenting with haematological indices suggestive of IDA and/or ACD following World Health Organisation (WHO) standard case definitions were identified among samples coming to the Haematology laboratory for routine investigations. Serum hepcidin, serum ferritin, serum iron and total iron binding capacity (TIBC) were assessed. Demographic data was obtained from specimen requisition forms. Results: Of the 66 participants, 62.1% (n = 41) were females. IDA was more common among females (36.4%) than males (6.1%) while ACD was more common in males (19.7%) than females (12.1%). Iron Deficiency Anaemia participants had significantly lower hepcidin levels than ACD (p<0.001). There was a significant positive correlation between serum hepcidin and serum ferritin levels (p < 0.001). Conclusion: We found that IDA participants had significantly lower hepcidin levels than ACD and IDA/ACD combined. Therefore, serum hepcidin could be considered in diagnosing and distinguishing ACD from IDA or IDA/ACD as it also had high diagnostic sensitivity and specificity compared to other markers. Asian Journal of Medical Sciences Vol.9(1) 2018 15-20